Epigenetic Control of Gonadotropin Releasing Hormone Neurons - Kurian, Joseph R.; Terasawa, Ei (Frontiers in Endocrinology, 2013)
Epigenetic modifications to the genome, including DNA methylation and histone modifications, occur in response to external stimuli. Reproductive function is highly sensitive to environmental conditions including season, diet, hormonal changes, and exposure to chemical contaminants. GnRH neurons, which play a key role in reproduction, are particularly sensitive to various environmental stimuli. We recently reported that the rhesus monkey GnRH gene exhibits distinct epigenetic differentiation during embryonic development. More recently, we further found that a similar epigenetic phenomenon occurs across puberty. In this article, we highlight recent findings, suggest implications of these findings (or potential mechanisms) and then discuss current challenges as well as future work. Consequently, this review will provide background to understand the epigenetic control of GnRH neurons as a link between the environment and reproductive function.